2009
DOI: 10.1111/j.1751-7915.2009.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of active microorganisms inhabiting a bioleaching industrial heap of low‐grade copper sulfide ore monitored by real‐time PCR and oligonucleotide prokaryotic acidophile microarray

Abstract: SummaryThe bioleaching of metal sulfide has developed into a very important industrial process and understanding the microbial dynamic is key to advancing commercial bioleaching operations. Here we report the first quantitative description of the dynamic of active communities in an industrial bioleaching heap. Acidithiobacillus ferrooxidans was the most abundant during the first part of the leaching cycle, while the abundance of Leptospirillum ferriphilum and Ferroplasma acidiphilum increased with age of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 59 publications
0
51
0
Order By: Relevance
“…We tested qPCR assays reported in the literature to target Acidithiobacillus , Leptospirillum and Sulfobacillus species (e.g., Liu et al, 2006; Remonsellez et al, 2009; Zhang et al, 2009) and found that most of them were only specific on genus-level or not specific for the desired species (results not shown). Thus we designed new qPCR assays targeting the species of the KCC consortium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We tested qPCR assays reported in the literature to target Acidithiobacillus , Leptospirillum and Sulfobacillus species (e.g., Liu et al, 2006; Remonsellez et al, 2009; Zhang et al, 2009) and found that most of them were only specific on genus-level or not specific for the desired species (results not shown). Thus we designed new qPCR assays targeting the species of the KCC consortium.…”
Section: Discussionmentioning
confidence: 99%
“…They comprise culture-dependent (plating, MPN counts) and biomolecular approaches such as the genetic fingerprinting techniques, terminal restriction fragment length polymorphism (T-RLFP; Wakeman et al, 2008), capillary electrophoresis single-strand conformation polymorphism (CE-SSCP; Foucher et al, 2003), denaturating gradient gel electrophoresis (DGGE; Demergasso et al, 2005; Halinen et al, 2009), microscopic methods like fluorescence in situ hybridization (FISH and CARD-FISH, Schippers et al, 2008), microarray approaches (e.g., Garrido et al, 2008; Remonsellez et al, 2009), quantitative real-time PCR (qPCR; Liu et al, 2006; Zhang et al, 2009), and next generation sequencing techniques (e.g., Cardenas et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection or quantification of the Ferroplasmaceae in these environments was done mostly using small subunit (SSU) rRNA-targeting analyses, such as 16S rRNA gene clone libraries' sequencing, amplified rRNA gene restriction analysis (ARDRA) profiling, real-time quantitative PCR, restriction fragment length polymorphism (RFLP) or fluorescence in situ hybridization (FISH), and oligonucleotide microarray analysis, all of which revealed the presence of these archaea in a number of pyritic/arsenopyritic, gold-arsenopyritic/chalcopyritic, and lead-, zinc-, and copper-containing mines across all continents (11,24,26,45,46,51,55,56,57,58). Clones related to the family Ferroplasmaceae have also been documented in further natural sulfide-rich ecosystems, e.g., in the snottites, i.e., the stalactite-like formations of microbial origin taken from the walls of Frasassi Cave and in the Rio Garrafo cave systems, both located in Italy, where acidic microenvironments were formed as a result of sulfide oxidation (38).…”
mentioning
confidence: 99%
“…The Species-Less model may apply to the case for pathogens, where immune-escape mutations may each constitute a new ecotype (Achtman and Wagner, 2008;Cohan, 2010). Also, the Species-Less model may apply in cases where an environment undergoes a succession process, where organisms at a site must adapt to rapidly changing conditions, for example the successions that occur on mine tailings, with pH and oxidation levels changing predictably and quickly (Remonsellez et al, 2009). …”
Section: Models Of Bacterial Speciationmentioning
confidence: 99%